Difference between Mechanical Alignment in Navigation and Scanogram during Total Knee Arthroplasty - Rohan Bhimani; Fardeen Bhimani; Preeti Singh (Advances in Orthopedics)
Introduction. Malpositioning of the implant results in polyethylene wear and loosing of implant after total knee arthroplasty. Scanogram is often used for measurement of limb alignment. Computer navigation provides real time measurements and thus, the aim is to see any association pre- and postoperatively between coronal alignments measured on scanogram to computer navigation during total knee arthroplasty. Material and Methods. We prospectively gathered data of 200 patients with advanced degenerative symptomatic arthritis, who were consecutively selected for primary total knee arthroplasty with computer navigation. Every patient’s pre- and postoperative scanogram were compared to the intraoperative computer navigation findings. Results. The results show that the preoperative mean mechanical axis on navigation was 10.65° (SD ± 6.95) and on scanogram it was 10.38° (SD ± 6.89). On the other hand, the mean postoperative mechanical axis on navigation was 0.69° (SD ± 0.87) and on scanogram it was 2.73° (SD ± 2.10). Preoperatively, there was no significant difference (p value = 0.46) between the two. However, the postoperative outcomes suggest that there was a noteworthy difference, with no correlation between the mean Hip-Knee Ankle Axis (HKA) and intraoperative mechanical axis (p value <0.0001). Conclusion. Postoperative mechanical alignment values after total knee arthroplasty are lower on navigation than measured on standing full length hip to ankle scanogram.